A Descriptive Study on the Role of the Post Office in Mail Services in the Digitalization Era: The Post Office at Jl. Pelita IV, Medan Perjuangan - br. Saragih, Renita; Simanjuntak, Francisco; Purba, Tresya Indriani; Hutasoit, Elli Novita (Bahasa Indonesia Prima, 2025)
Technological developments in the digital era have changed the communication system, including mail delivery. PT Pos Indonesia as a state-owned enterprise in the field of postal and financial services faces challenges in the form of a decrease in mail volume. However, the delivery of official documents such as power of attorney and land certificates still requires postal services because of its legality. Pos Indonesia's advantage lies in its service coverage to remote areas and operations on holidays. This study uses a descriptive qualitative method with interview techniques with one Pos Indonesia employee, Fatimah Rengkuti, at the Post Office on Jl. Pelita IV, Medan. The results show that despite declining public interest, Pos Indonesia still plays an important role through digital service innovations such as the PosPay application to maintain relevance in the digital era.